2011
DOI: 10.1152/ajpheart.00954.2010
|View full text |Cite
|
Sign up to set email alerts
|

Exercise limits the production of endothelin in the coronary vasculature

Abstract: We previously demonstrated that endothelin (ET)-mediated coronary vasoconstriction wanes with increasing exercise intensity via a nitric oxide- and prostacyclin-dependent mechanism (Ref. 23). Therefore, we hypothesized that the waning of ET coronary vasoconstriction during exercise is the result of decreased production of ET and/or decreased ET receptor sensitivity. We investigated coronary ET receptor sensitivity using intravenous infusion of ET and coronary ET production using intravenous infusion of the ET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…distribution of blood flow over the coronary vascular bed. 36,37 We observed an increase in coronary flow velocity during Ex1, where MR continued to fall, after an initial slight increase at the start, suggesting progressive vasodilation of the coronary vascular bed with increasing workload. It has been shown that persistent vasomotor tone is present throughout the coronary microcirculation even during ischemia, with substantial vasodilator reserve remaining within the exercising vascular bed of a hypo-perfused region.…”
Section: Persistent Decrease In Coronary Microvascular Resistance Indmentioning
confidence: 70%
“…distribution of blood flow over the coronary vascular bed. 36,37 We observed an increase in coronary flow velocity during Ex1, where MR continued to fall, after an initial slight increase at the start, suggesting progressive vasodilation of the coronary vascular bed with increasing workload. It has been shown that persistent vasomotor tone is present throughout the coronary microcirculation even during ischemia, with substantial vasodilator reserve remaining within the exercising vascular bed of a hypo-perfused region.…”
Section: Persistent Decrease In Coronary Microvascular Resistance Indmentioning
confidence: 70%
“…Enhanced ventricular relaxation reduces microvascular compression,28 which helps lower MVR. Despite vasoconstriction of the epicardial stenosed segment during exercise29 (evidenced by increased stenosis severity in our study), parallel intense vasodilatation of resistance vessels during exercise30 overcomes this, resulting in further adaptive reduction of MVR.…”
Section: Discussionmentioning
confidence: 55%
“…ET-mediated coronary vasoconstriction is reduced with increasing exercise intensity, and decreased ET production during exercise likely contributes to the metabolic coronary vasodilation (24). Moreover, ET-1 contributes to the progression of cardiopulmonary pathology in rats (25).…”
Section: Discussionmentioning
confidence: 99%